Genetic solutions to cultural problems?. (13th September 2022) - Newson, Lesley; Richerson, Peter J.
Abstract: In theory, observed correlations between genetic information and behaviour might be useful to members of the WEIRD (western, educated, industrialized, rich, and democratic) populations. Guiding young people to choose educational opportunities that best match their abilities would benefit both the individual and society. In practice, however, such choices are far more profoundly limited by the culture people have inherited than their genes.